Pengaruh Gaya Kepemimpinan Dan Komunikasi Terhadap Kinerja Karyawan Pada Klinik Utama Dan Apotek Prima Husada Cinere Depok - Ricky Apriyano; Shella Puspita Sari (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the partial and simultaneous influence of leadership and communication styles on employee performance at the Prima Husada Cinere Depok Main Clinic and Pharmacy. This research method used a quantitative description method, with a questionnaire as the data collection technique. The population of the study was 63 employees of the Prima Husada Cinere Depok Main Clinic and Pharmacy. Therefore, the sample in this study was 63 people. Using the saturation technique, a sample of 63 respondents was taken. Data analysis used validity tests, reliability tests, classical assumption tests, multiple regression analysis, multiple correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. There was an influence of leadership style (X1) with a tcount of 10.103 and a significance level of 0.000. Because the tcount was greater than the ttable (10.103 > 2.000) and the significance level was less than 5%, Ha was accepted and H0 was rejected. It can be stated that leadership style (X1) has a significant effect on employee performance (Y). There is an influence of Communication (X2) with a tcount of 12.193 and a significance level of 0.000. Because the tcount is greater than the ttable (12.193 > 2.000) and the significance level is less than 5% (0.000), Ha is accepted and H0 is rejected. It can be stated that Communication (X2) has a significant effect on Employee Performance (Y). There is a significant influence between Leadership Style and Communication on Employee Performance. Based on the analysis results in the table above, namely the ANOVA test, the Fcount value is 421.217 while the Ftable (α 0.05) for n = 60 is 2.76. So, Fcount > Ftable (α 0.05) or 421.217 > 2.76, with a significance level of 0.000 because 0.000 < 0.05, it can be said that Leadership Style (X1), Communication (X2) and together influence Employee Performance (Y).